KIPRAH KH. YUSUF SALIM FAQIH DALAM PERKEMBANGAN PENDIDIKAN DI PONDOK PESANTREN BAITUL ARQOM AL ISLAMI PACET KABUPATEN BANDUNG (1982-2009) - Widia Aprianti Rukmana, - (2023)
The development of pesantren cannot be separated from the role of a kiai in leading the pesantren. Same with KH. Yusuf Salim Faqih, who has a role in the Baitul Arqom AlIslami boarding school, is the background of this research. The discussion of this research includes the biography of KH. Yusuf Salim Faqih during his lifetime, the role of KH. Yusuf Salim Faqih in the development of Islamic boarding schools with the establishment of the Arabic Language Institute, and the development of education at the Baitul Arqom AlIslami Islamic boarding school from 1982 to 2009. The purpose of this research is to determine the role of KH. Yusuf Salim Faqih in the development of the Baitul Arqom AlIslami boarding school. The method in this study is the historical method, which has four stages, namely: heuristics, source criticism, interpretation, and historiography. Through this research it is known that, first, KH. Yusuf Salim Faqih is the 4th leader at the Baitul Arqom Al-Islami boarding school, KH. Yusuf Salim founded the Arabic Language Institute in 1982. Second, with the establishment of the Arabic Language Institute, it brought changes to Islamic boarding schools. Third, during its development, Islamic boarding schools changed the curriculum at least twice, the first from 1982 to 1992 using the 1984 curriculum. From 1992 to 2009, Islamic boarding schools replaced the curriculum with the 1994 curriculum. During this period there were changes, classrooms increased every year. the year, in 1986 the establishment of the high school of syari'ah science (STIS). The conclusion that researchers can get is regarding the role played by KH. Yuusf Salim Faqih during a change at the Baitul Arqom Al-Islami boarding school. The recommendation given by the author is that students can research the Baitul Arqom boarding school because there are still many things that have not been discussed and researched.